Foundations of kinesiology a modern integrated approach - Murray, Tinker D.; Eldridge, James A.; Kohl, Harold W. III (Boston, MA Cengage Learning, 2019)
Teaches undergraduates to incorporate evidence-based practice strategies as they prepare for specific Kinesiology careers. Combining digital and traditional delivery methods, the authors provide a solid foundation in basic Kinesiology and subdisciplines such as biomechanics, motor learning, exercise physiology and public health. They also emphasize skills needed for effective careers in personal training, occupational and physical therapy, athletic training, sports psychology and sports management. A running case requires students to create solutions that promote physically active lifestyles for various circumstances. MindTap Health propels students from memorization to mastery with numerous digital learning tools including Career Insights Videos.
Module 1: INTRODUCTION, DEFINITIONS, CAREERS AND EVIDENCE-BASED PRACTICES.1. Physical Activity and Society -- Why Do You Need This Course? Lesson 1. Physical Activity and Society. Lesson 2. What is Kinesiology?2. Current Trends and Kinesiology Careers. Lesson 1. Integration of Professional Skills for Various Kinesiology Careers. Lesson 2. Career Planning for Kinesiology.3. Evidenced-Based Practice in Kinesiology. Lesson 1. Definitions, Evidence-Based Practice and the Scientific Method, and the Mechanics of Evidence-Based Practice (EBP). Lesson 2. Examples of Evidence-Based Practices in Kinesiology.Module 2: COMMON DELIVERABLES FOR KINESIOLOGY MAJORS.4. The Physical Activity Continuum: Applications to Kinesiology. Lesson 1. Physical Activity and Exercise Over the Lifespan. Lesson 2. Examples of Applying Training Fundamentals in Kinesiology Sub-disciplines.5. The Physical Activity Continuum: Integration of Aerobic Training Principles. Lesson 1. Integration of Aerobic Principles into Kinesiology. Lesson 2. Examples of Applying Aerobic Principles in Kinesiology Sub-disciplines.6. The Physical Activity Continuum: Integration of Strength and Conditioning Principles for the Musculoskeletal System. Lesson 1. Integration of Strength and Conditioning Principles into Kinesiology. Lesson 2. Examples of Applying Strength and Conditioning Principles in Kinesiology Sub-disciplines.7. The Physical Activity Continuum: Integration of Energy Balance and Body Composition Principles. Lesson 1. Integration of Energy Balance and Body Composition Basics into Kinesiology. Lesson 2. Examples of Applying Energy Balance and Body Composition Basics in Kinesiology Sub-disciplines.8. Integration of Mental Health, Psychology and the Physical Activity Continuum. Lesson 1. Integration of Mental Health and the Physical Activity Continuum. Lesson 2. Examples of Applying Mental Health and Physical Activity Basics in Relationship to the Kinesiology Sub-disciplines.Module 3: COMMON PROFESSIONAL SETTINGS AND OCCUPATIONAL CHALLENGES.9. Integration of Kinesiology and Physical Activity into the Workplace. Lesson 1. Integration of Business and Industry with the Principles of Physical Activity and Kinesiology. Lesson 2. Examples of Applying Business and Industry Principles of Physical Activity in Relationship to the Kinesiology Sub-disciplines.10. Integration of Kinesiology with Leisure Time, Recreation and Personal Training. Lesson 1. Integration of Leisure Time, Recreation and Personal Training with the Principles of Physical Activity and Kinesiology. Lesson 2. Examples of Applying Leisure Time, Recreation and Personal Training Principles of Physical Activity Basics in Relationship to the Kinesiology Sub-disciplines.11. Integration of Kinesiology and Physical Activity in Schools. Lesson 1. Physical Activity in Schools. Lesson 2. Examples of Applying Kinesiology Sub-disciplines in School Settings. 12. Sport. Lesson 1. Integration of Sports with the Principles of Physical Activity and Kinesiology. Lesson 2. Examples of Applying Sport Principles of Physical Activity Basics in Relationship to Kinesiology Sub-disciplines.13. Integration of Kinesiology in Transportation and Home Environments. Lesson 1. Integration of Transportation and Home Environment with the Principles of Physical Activity and Kinesiology. Lesson 2. Examples of Applying Transportation and Home Environment Principles of Physical Activity Basics in Relationship to the Kinesiology Sub-disciplines.Module 4: PROFESSIONAL ETHICS, LEADERSHIP AND CONTINUING EDUCATION.14. Ethics and Evidence-Based Decisions: Using Best Practices to Lead the Profession into the Future. Lesson 1. The Kinesiology Profession. Lesson 2. Evidence-Based Practices and Challenges for Kinesiology Professionals. 15. Best Practices for Leadership in the Kinesiology Profession. Lesson 1. Leadership in Kinesiology. Lesson 2. Applying Leadership Skills to the Kinesiology Sub-disciplines.16. Summary of Key Concepts and Your Future in the Kinesiology Profession. Lesson 1. Unifying Themes in Kinesiology. Lesson 2. Final Thoughts.
Includes bibliographical references (pages 364 - 370) and index.
Keywords: Kinesiology, Applied; Kinesiology -- Textbooks; Human mechanics -- Textbooks